2020
DOI: 10.1139/cjfas-2019-0105
|View full text |Cite
|
Sign up to set email alerts
|

Horizon scan of conservation issues for inland waters in Canada

Abstract: Horizon scanning is a systematic approach increasingly used to explore emerging trends, issues, opportunities, and threats in conservation. We present the results from one such exercise aimed at identifying emerging issues that could have important scientific, social, technological, and managerial implications for the conservation of inland waters in Canada in the proximate future. We recognized six opportunities and nine challenges, for which we provide research implications and policy options, such that scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Many environmental horizon-scanning projects focus on these latter emerging issues (e.g. Kark et al 2016;Pérez-Jvostov et al 2020;Sutherland et al 2020;Wintle et al 2017). However, we felt it was valuable to also highlight persistent issues, regardless of novelty, to give a complete picture of the challenges and opportunities facing Mediterranean wetlands (van Rij 2010; Cranfield University 2018).…”
Section: Scopementioning
confidence: 99%
See 1 more Smart Citation
“…Many environmental horizon-scanning projects focus on these latter emerging issues (e.g. Kark et al 2016;Pérez-Jvostov et al 2020;Sutherland et al 2020;Wintle et al 2017). However, we felt it was valuable to also highlight persistent issues, regardless of novelty, to give a complete picture of the challenges and opportunities facing Mediterranean wetlands (van Rij 2010; Cranfield University 2018).…”
Section: Scopementioning
confidence: 99%
“…Contemporary challenges for Mediterranean wetlands include rapid urbanisation, increased water usage, climate change and land conversion (MWO 2018). Although several foresight projects have been carried out with implications for the Mediterranean (Kark et al 2016;Moreira et al 2019), aquatic systems (Brown et al 2010;Pérez-Jvostov et al 2020) and environmental conservation more generally UNEP 2017;Ockendon et al 2018;Sutherland et al 2020;Esmail et al 2020), there remains a need for analyses focused on the nexus of these topics: Mediterranean wetlands and their conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Another challenge is resistance from politicians and lobby groups to implementing legislative frameworks that adequately protect freshwater resources. It is clear that prioritization of high-level initiatives like the ERP at the level of BOX 2 Operationalizing practitioners to "protect and restore critical habitat (strategy 4)" for the benefit of freshwater biodiversity-A Canadian context Despite having some of the longest stretches of free-flowing rivers on Earth (Grill et al, 2019), Canadian freshwater systems face a number of threats (e.g., dams, pollution) that risk freshwater biodiversity (Pérez-Jvostov et al, 2020). Here, we outline a conceptual diagram highlighting the main actors and the roles they must play to achieve strategy 4 ("protecting and restoring critical habitat") of the Emergency Recovery Plan for freshwater biodiversity (ERP) in Canada.…”
Section: Policymentioning
confidence: 99%
“…It is estimated that just 37% of large rivers over 1,000 km in length remain free flowing (Grill et al, 2019), and many of the world's largest, most biodiverse rivers (e.g., Mekong, Congo, Amazon) are slated for new or intensified hydropower development in the coming years or decades. In addition to the known threats facing freshwater ecosystems, a number of recently recognized or emerging threats have been identified that can further degrade aquatic habitats worldwide (e.g., salinization of freshwater, microplastic and nanoparticle pollution; Reid et al, 2019; Pérez‐Jvostov et al, 2020). Regardless of the mechanisms, the global decline of freshwater ecosystems is compromising the many services they provide to humans (Dodds, Perkin, & Gerken, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…is not yet available (Pérez-Jvostov et al 2020). For example, the WWF Canada Watershed reports focus on indicator species (e.g., fish and macroinvertebrates) with the goal of assessing ecosystem health, but not total biodiversity (WWF-Canada 2020).…”
mentioning
confidence: 99%